Proceedings of the 11th Asia Pacific Conference on Computer Human Interaction 2013
DOI: 10.1145/2525194.2525213
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of multimodal input interaction based on goals

Abstract: Today applications demand newer and newer ways through which humans can interact with the system for effective and natural interaction. Each interaction modality have unique features and supports different interaction goals, which makes them logically appropriate for specific types of interaction necessary for different applications. With several multimodal input technologies now being available for users, a challenge is to design optimal combinations of multiple modalities for specific tasks. Also, it is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…In fact, some previous studies explored the factors influencing the choice among different modalities such as speech, text, and gestures. Factors such as efficiency, accuracy, privacy and security (Himmelsbach et al, 2015), user characteristics (Dumas et al, 2009;Ghosh and Joshi, 2013;Schüssel et al, 2013;Schaffer et al, 2015), attitudes toward technology, and quality perceptions and personality factors (Wechsung, 2014) have been shown to impact modality selection. Jian et al (2013) demonstrated the potential of multimodal interaction (interacting with multiple modalities such as text and speech) for older adults.…”
mentioning
confidence: 99%
“…In fact, some previous studies explored the factors influencing the choice among different modalities such as speech, text, and gestures. Factors such as efficiency, accuracy, privacy and security (Himmelsbach et al, 2015), user characteristics (Dumas et al, 2009;Ghosh and Joshi, 2013;Schüssel et al, 2013;Schaffer et al, 2015), attitudes toward technology, and quality perceptions and personality factors (Wechsung, 2014) have been shown to impact modality selection. Jian et al (2013) demonstrated the potential of multimodal interaction (interacting with multiple modalities such as text and speech) for older adults.…”
mentioning
confidence: 99%